Impactos socioambientais da coleta de Castanha-do-Pará (Bertholletia excelsa, Bonpl.) na reserva biológica do Rio Trombetas e entorno, Oriximiná, PA - LOBO, Mateus Feitosa Siqueira (Universidade Federal do Oeste do Pará, 2021)
The analysis of an extractive activity of great importance in the Amazon biome, as is the collection of Brazil nut on an Integral Protection Conservation Unit - is critical in the current the current overlay scenario territorial interests. This study aimed to analyze the environmental impacts associated with this activity in the Biological Reserve of Trombetas (Oriximiná, Pará) to generate data relating to the dynamics of use of natural resources, through the quantification of the economic importance of the nut collection for families quilombolas extractivists, verification of possible secondary impacts of activities on the environment (waste and landscape changes) and identification of impacts related to the regeneration of the Brazil nut tree. They used concepts of territory and territoriality as a theoretical and methodological basis, combined with traditional communities concepts and inter-related research on the extractives activity of Brazil nut. A questionnaire was applied to obtain socioeconomic data and change the landscape of the communities involved in extractive activities. To analyze the impacts of the activity in the regeneration of nut trees were inventoried 14 plots castanhal areas, 14 plots of areas not castanhal and 12 temporary camps were inspected in order to verify the presence of regenerating individuals in these sectors. It is attested that the collection of Brazil nuts is the most important NTFP in the composition of the income of these communities, adding 28% on average in the composition of total gross income. The average extractivists in the camps was 5.4 ± 2.6 gatherers, the average open area was 297.4 ± 239.1 m² (<0.03 hectares), canopy opening level average of 46.6 ± 22.81% and the average age of the camps was 11.2 ± 22.8 years. The average size of the area of the camps is low, with a lower average 0.3 hectares, maximum of 962 m² (about 0.1 ha) to 49 m² (0, 005 ha), allowing certain shading the area, because opening average canopy does not exceed 50%. As for solid waste, 54% reported that burn waste, and only 26% of the interviewed assured that collect the inert waste and carry to the advanced ICMBIO bases, with another 11% that take to the community their waste, 6% bury near the camps and only 3% leave exposed in the common areas. The total number of regenerants individuals found in environments investigates was 43 individuals, the mean height was 0.69 ± 1.08 cm and the average DAP was 0.94 ± 2.66 cm. Seedlings were detected in 3 environments studied (track, camp and castanhal). The environment that had greater representation of seedlings was the trail of nut extractive (11 of 12 sampled units), with a mean of 3.1 ± 3.1 h-1 seedlings. In contrast, the other two environments studied (camp and castanhal), seedlings were identified only in 5 and 4 sampling units, representing 42% and 33% of the total respectively. Finally, it was observed that the issues relating to territorial demands in question, control of resources and conservation measures within the REBIO should embrace traditional knowledge of these residents and users of the territory, promoting the development of these communities.